Edukasi Peningkatan Pemahaman Kesehatan Remaja Karang Taruna Desa Cepagan Melalui Pengembangan Minuman Teh Daun Kemangi: Youth Karang Taruna Cepagan Village Health Education to Increase Understanding Through the Development of Basil Leaf Tea Drinks - Endriyatno, Nur Cholis; Walid, Muhammad; Sasongko, Aditya Dimas Wahyu; Himawan, Ryan; Ariani, Annastasya Putri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
In Cepagan Village, Warungasem District, Batang Regency, there are many stems of basil plants found around the yard. Basil leaves are known to have the benefit of helping lower blood pressure. From field observations, many people in the village have a history of hypertension. Apart from that, people don't know how to prepare basil leaf tea as an alternative to help lower blood pressure. The target of community service was chosen to be young people from youth organizations considering that there were no activities in the health sector and also based on teenagers' ability to grasp understanding more easily than the elderly. Given the problems and the abundant availability of natural materials, there is a need for community service in the area. This service aims to improve the health of the people of Cepagan Village through Karang Taruna youth by providing education to increase health understanding through drinking basil leaf tea to help reduce hypertension. Service is carried out by presenting material and interactive discussions. The number of service participants was 22 participants. The pretest and posttest describe participants' understanding before and after service. The evaluation results show that the pretest score (5-14%) increased on the posttest (91-100%). So it can be concluded that this community service was successful.